Modern Technologies of Inclusive Higher Education - I. A. Kuvshinova; E. L. Mitsan; E. M. Razumova; E. I. Shuleva (Высшее образование в России)
Inclusive educational space is an essential part of modern education. Many higher educational institutions are faced with a lack of professional skills in this area. The article aims at presenting the technologies of inclusive education implemented at G.I. Nosov Moscow State Technical University. A team of scientific and pedagogical workers applies innovative inclusive technologies for training students with special educational needs majoring in psychological and pedagogical education. The applied classroom methods such as association method, training work, including role games and art-therapy and others, enable to present the material in special educational form which is easy for perception, to develop motor activity, as well as team skills and creativity.The article dwells on an experience of using educational portal and electronic educational resources, which should be viewed as an effective means of improving the quality of educational activities in inclusive educational space.The authors present the results of an empirical study for the assessment of the quality of student performance depending on their attendance of the educational portal.